A macromolecular silane coupling agent for polyimide composite materials and its preparation method and application
By designing the reaction of macromolecular silane coupling agent with the fiber surface, a strong tangle is formed, which solves the problem of weak interaction between small molecules and coupling agents, significantly improves the mechanical and thermal stability of polyimide composites, and achieves high Preparation of performance fiber/polyimide composites.
Patent Information
- Application Number
- CN202411251665.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing small molecule silane coupling agents have weak interactions with polyimide-based composite materials, resulting in unsatisfactory reinforcement effects of composite materials and are difficult to meet the performance requirements in high temperature environments.
Design and synthesize macromolecular silane coupling agents with polyimide polymer framework and flexible winding properties, and improve their physical and mechanical properties through specific preparation methods to modify fibers to prepare high-performance fibers/polyacyl Imine composite material.
The macromolecular silane coupling agent reacts with the hydroxyl group on the surface of the fiber to form stronger physical entanglement, which significantly improves the mechanical properties and thermal stability of the composite material, and achieves higher fiber-matrix compatibility and material properties.
Smart Images

Figure CN118772407B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a macromolecular silane coupling agent for polyimide composite materials and a preparation method and application thereof. Background Art
[0002] Composite materials are a new type of high-performance material, which is made of organic polymer materials as the matrix and continuous fibers as the reinforcement material by composite technology. It has a structure of two or more phases, and its performance is significantly better than the original components. In the field of aerospace, high-performance resin-based composite materials have become an indispensable material in modern society due to their advantages such as high modulus, high specific strength, fatigue resistance, strong corrosion resistance and unique designability, and gradually replaced traditional materials such as titanium, aluminum alloy and steel. At present, the widely used high-performance resin-based composite materials mainly include composite materials with epoxy resin, phenolic resin and polyimide resin as the matrix. Among many polymers, polyimide composite materials show excellent comprehensive properties at high temperatures, can be used for a long time at 280-400℃, and can be used as load-bearing components in high temperature environments. In recent years, polyimide composite materials have been widely used in fields such as aircraft engines, showing their excellent performance under extreme conditions.
[0003] At present, the coupling agents used in polyimide-based composite materials are mainly small molecule silane coupling agents. Although a certain reinforcement effect can be achieved after modifying the surface of the reinforcement material, due to compatibility issues, the interaction efficiency between the fiber and the matrix resin is low, so the reinforcement effect is also very limited. Compared with small molecule coupling agents, macromolecular coupling agents have relatively long molecular chains. When used to modify polyimide-based composite materials, they can produce stronger physical entanglement with the polymer matrix to achieve effective reinforcement; and the structure and composition of the synthesized macromolecular coupling agents can be changed by design to control and improve the performance of the material.
[0004] Therefore, providing a macromolecular silane coupling agent and a preparation method thereof that can enhance the performance of polyimide composite materials is a technical problem that those skilled in the art urgently need to solve. Summary of the invention
[0005] In view of this, the present invention is based on the actual needs and future development of polyimide (PI) composite materials to solve the problem that the existing small molecule silane coupling agent has weak interaction with PI resin and the reinforcement effect of the composite material is not ideal. Based on molecular design, a macromolecular silane coupling agent with a polyimide polymer skeleton and flexible winding characteristics is synthesized for use in modifying fibers to prepare polyimide-based composite materials. By controlling the structure of the macromolecular coupling agent, its physical and mechanical properties and processing properties are improved to obtain a high-performance fiber / polyimide composite material.
[0006] To achieve the above object, the present invention adopts the following technical solution;
[0007] A macromolecular silane coupling agent for a polyimide composite material, wherein the macromolecular silane coupling agent is any one of the following general formulas (I) to (III):
[0008]
[0009] (Ⅰ)
[0010]
[0011] (Ⅱ)
[0012]
[0013] (III)
[0014] In general formula (I) to general formula (III), n≥3, R1, R2, R3 are independently selected from C1~C18 linear or branched saturated alkyl groups, and R4 is selected from C1~C18 linear or branched saturated alkyl groups or branched or branched alkanes with heteroatoms.
[0015] The present invention also provides a method for preparing the above-mentioned macromolecular silane coupling agent, comprising the following steps:
[0016] The raw material A and the raw material B are mixed under anhydrous and oxygen-free conditions and added to an organic solvent for reaction, and then end-capped with 2-aminopyridine, a polyimide solution is obtained by chemical imidization, and then ethanol is added to precipitate the polyimide to obtain an end-capped product, and the end-capped product is washed and dried and then subjected to a transfer amidation reaction with the raw material C to prepare a macromolecular silane coupling agent;
[0017] The raw material A is a diamine, the raw material B is a dibasic acid anhydride, and the raw material C is a silane coupling agent with an amino terminal group.
[0018] Furthermore, the diamine is diaminodiphenyl ether or 1,3-bis(4-aminophenoxy)benzene; and the dibasic acid anhydride is hexafluorodianhydride or 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride.
[0019] Furthermore, the organic solvent is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, xylene and tetrahydrofuran.
[0020] Further, the reaction temperature of the raw material A and the raw material B is 80-140° C., and the reaction time is 4-6 hours;
[0021] The molar ratio of raw material A to raw material B is 1:0.75-1.
[0022] Furthermore, the reaction of the end-capped product and the raw material C is carried out under the catalysis of a dehydrating agent and a catalyst.
[0023] Furthermore, the dehydrating agent is acetic anhydride, and the catalyst is triethylamine or pyridine.
[0024] Further, the reaction temperature of the end-capped product and the raw material C is 80-140° C., and the reaction time is 12-24 h;
[0025] The molar ratio of the end-capping product to the raw material C is 1:1-3.
[0026] Preferably, the macromolecular silane coupling agent is prepared by the following method:
[0027] (1) At room temperature, add raw material A to a reaction bottle equipped with a stirring device, a condensing device, and a N2 atmosphere, add an organic solvent and stir, and after raw material A is completely dissolved, add raw material B to the reaction bottle. After the raw materials are completely dissolved, continue to react at room temperature to obtain a polyamic acid solution; add 2-aminopyridine and continue to react for 2 to 4 hours to cap the polyamic acid, wherein the molar amount of 2-aminopyridine added is twice the theoretically calculated polyamic acid molecular chain. Use the chemical imidization method, add a dehydrating agent and a catalyst to the polyamic acid system, heat and stir for 12 to 24 hours to obtain a polyimide solution, add ethanol to precipitate, wash and dry to obtain a 2-aminopyridine-capped polyimide;
[0028] (2) Add 2-aminopyridine-terminated polyimide oligomer to a reaction bottle equipped with a stirring device, a condensing device and a N2 atmosphere, add an organic solvent and stir to completely dissolve it, then add raw material C, heat and reflux to react, then add ethanol to precipitate the product, centrifuge and wash and dry to obtain the macromolecular silane coupling agent.
[0029] The beneficial effects of the present invention are as follows: the macromolecular silane coupling agent prepared by the present invention has a relatively long molecular chain, a polyimide polymer skeleton and flexible entanglement characteristics. When used for modification of polyimide-based composite materials, both ends can react with the hydroxyl groups on the fiber surface, and the long chain can produce stronger physical entanglement with the polyimide matrix, thereby effectively enhancing the mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the macromolecular silane coupling agent prepared by the present invention;
[0031] Figure 2The scanning electron microscope images of the cross-section of the 3 mm carbon fiber reinforced polyimide material treated differently according to the present invention; wherein (a) is an untreated sample, (b) is a sample treated with a small molecule silane coupling agent KH550, (c) is a sample treated with a macromolecular silane coupling agent 6FDA-ODA-KH550, (d) is a sample treated with a macromolecular silane coupling agent a-ODPA-ODA-KH550, and (e) is a sample treated with a macromolecular silane coupling agent a-ODPA-134APB-KH550;
[0032] Figure 3 The mechanical properties of 3mm carbon fiber reinforced polyimide composites treated with different coupling agents of the present invention;
[0033] Figure 4 The thermal weight loss curves of 3mm carbon fiber reinforced polyimide composites treated with different coupling agents of the present invention;
[0034] Figure 5 The DSC curves of 3mm carbon fiber reinforced polyimide composites treated with different coupling agents of the present invention;
[0035] Figure 6 The scanning electron microscope images of the cross-section of the 3 mm glass fiber reinforced polyimide material after different treatments of the present invention, wherein (a) is an untreated sample, (b) is a sample treated with a small molecule silane coupling agent KH550, (c) is a sample treated with a macromolecular silane coupling agent 6FDA-ODA-KH550, (d) is a sample treated with a macromolecular silane coupling agent a-ODPA-ODA-KH550, and (e) is a sample treated with a macromolecular silane coupling agent a-ODPA-134APB-KH550;
[0036] Figure 7 The mechanical properties of 3mm glass fiber reinforced polyimide composite materials treated with different coupling agents of the present invention;
[0037] Figure 8 The thermal weight loss curves of 3mm glass fiber reinforced polyimide composite materials treated with different coupling agents of the present invention;
[0038] Fig. 9 These are the DSC curves of the 3mm glass fiber reinforced polyimide composite material treated with different coupling agents of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A macromolecular silane coupling agent (6FDA-ODA-KH550) for polyimide composite materials, the structural formula is as follows:
[0042]
[0043] The specific preparation steps are:
[0044] (1) At room temperature, 6.00 g (0.03 mol) of diaminodiphenyl ether was added to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere, and 150 g of N,N-dimethylacetamide (DMAc) was added and stirred to dissolve, and then 17.76 g (0.04 mol) of hexafluorodianhydride was added. After the raw materials were completely dissolved, the reaction continued for 4 h to obtain a polyamic acid solution. 1.88 g of 2-aminopyridine was added and the reaction continued for 2 h to cap the polyamic acid. A chemical imidization method was adopted, and 37.02 g (0.36 mol) of acetic anhydride and 36.42 g (0.36 mol) of triethylamine were added to the polyamic acid system as a dehydrating agent and catalyst, and stirred for 24 h to fully react to obtain a polyimide solution (referred to as 6FDA-ODA-2APY). Ethanol was poured into the solution to precipitate the product, which was filtered and ultrasonically cleaned 3 times. After drying at 80°C and vacuum dried for 24 h, a brown solid powder was obtained.
[0045] (2) At room temperature, add 24.2 g (0.01 mol) of 6FDA-ODA-2APY to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere, add 300 ml of DMAc and stir for 5 min to completely dissolve it, add 6.63 g (0.03 mol) of 3-aminopropyltriethoxysilane (KH550), and heat under reflux at 140°C for 24 h. After the reaction is completed, the product is precipitated with anhydrous ethanol, filtered, and centrifuged three times to remove 2-aminopyridine and unreacted KH550, and then dried at 80°C in vacuum for 24 h to obtain a macromolecular silane coupling agent, which is recorded as 6FDA-ODA-KH550.
[0046] Example 2
[0047] A macromolecular silane coupling agent (a-ODPA-ODA-KH550) for polyimide composite materials has the following structural formula:
[0048]
[0049] The specific preparation steps are:
[0050] (1) At room temperature, 6.00 g (0.03 mol) of diaminodiphenyl ether was added to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere, and 150 g of DMAc was added and stirred to dissolve, and then 12.4 g (0.04 mol) of 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride was added. After the raw materials were completely dissolved, the reaction was continued for 4 h to obtain a polyamic acid solution, and 1.88 g of 2-aminopyridine was added and the reaction was continued for 2 h to cap the polyamic acid. By chemical imidization, 37.02 g (0.36 mol) of acetic anhydride and 36.42 g (0.36 mol) of triethylamine were added to the polyamic acid system as a dehydrating agent and a catalyst. After stirring and reacting for 24 h, a polyimide solution (referred to as a-ODPA-ODA-2APY) was obtained. Ethanol was added to the solution to precipitate the product, which was filtered and ultrasonically cleaned three times. It was vacuum dried at 80 ° C for 24 h to obtain a brown solid powder.
[0051] (2) At room temperature, 18.8 g (0.01 mol) of a-ODPA-ODA-2APY was added to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere, and 300 ml of DMAc was added and stirred for 5 min to completely dissolve it. 6.63 g (0.03 mol) of 3-aminopropyltriethoxysilane was added and heated to reflux at 140°C for 24 h. After the reaction was completed, the product was precipitated with anhydrous ethanol, filtered, and centrifuged three times to remove 2-aminopyridine and unreacted KH550, and then dried at 80°C in vacuum for 24 h to obtain a macromolecular silane coupling agent, which was recorded as a-ODPA-ODA-KH550.
[0052] Example 3
[0053] A macromolecular silane coupling agent (a-ODPA-1,3,4-APB-KH550) for polyimide composite materials has the following structural formula:
[0054]
[0055] The specific preparation steps are:
[0056] (1) Under room temperature, 8.76 g (0.03 mol) of 1,3-bis(4-aminophenoxy)benzene was added to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere. 150 g of DMAc was added and stirred to dissolve. Then, 12.4 g (0.04 mol) of 2,3,3',4'-diphenylether tetracarboxylic dianhydride was added. After the raw materials were completely dissolved, the reaction was continued for 4 h to obtain a polyamic acid solution. 1.88 g of 2-aminopyridine was added and the reaction was continued for 2 h to cap the polyamic acid. 37.02 g (0.36 mol) of acetic anhydride and 36.42 g (0.36 mol) of triethylamine were added to the polyamic acid system as a dehydrating agent and a catalyst by chemical imidization method. The mixture was stirred for 24 h. After h of reaction, a polyimide solution (denoted as a-ODPA-1,3,4-APB-2APY) was obtained; ethanol was added to the solution to precipitate the product, which was filtered, ultrasonically cleaned 3 times, and vacuum dried at 80°C for 24 h to obtain a brown solid powder.
[0057] (2) At room temperature, 20.4 g (0.01 mol) of a-ODPA-1,3,4-APB-2APY was added to a 500 ml three-necked flask equipped with a stirring device, a condensing device and a N2 atmosphere, and 300 ml of DMAc was added and magnetically stirred for 5 min to completely dissolve it. 6.63 g (0.03 mol) of 3-aminopropyltriethoxysilane was added and heated to reflux at 140°C for 24 h. After the reaction was completed, the product was precipitated with anhydrous ethanol, filtered, and centrifuged three times to remove 2-aminopyridine and unreacted KH550, and then vacuum dried at 80°C for 24 h to obtain a macromolecular silane coupling agent, which was recorded as a-ODPA-1,3,4-APB-KH550.
[0058] Test Example 1
[0059] The macromolecular coupling agent obtained in Example 1-3 was subjected to hydrogen nuclear magnetic resonance spectroscopy, and the results were as follows: Figure 1 As shown:
[0060] In the figure, 2.5 ppm and 3.3 ppm are the peaks of deuterated DMSO and water respectively, and the peaks at 1.96 ppm, 2.78 ppm and 2.94 ppm are the peaks of residual DMAc. The hydrogen peaks of the three methylene groups on the aminopropyl group of KH550 are at 2.62 ppm, 1.43 ppm and 0.57 ppm respectively. The peaks at 1.15 ppm and 3.74 ppm are the peaks of the three hydrogen groups of the methyl groups on the three ethoxy groups and the two hydrogen groups of the methylene groups. The results show that KH550 is capped at both ends of the polyimide, and the macromolecular silane coupling agent is successfully prepared.
[0061] Test Example 2 Application of macromolecular silane coupling agent in Example 1-3 to modified reinforced carbon fiber
[0062] S1. Select short chopped carbon fibers with an average length of 3 mm. The surface of the carbon fibers is oxidized by nitric acid to produce oxygen-containing active groups such as hydroxyl groups to improve the surface activity: the surface of the carbon fibers is cleaned by soaking the fibers in anhydrous ethanol solution for 24 hours, ultrasonically treating them for 30 minutes, and vacuum drying. The dried carbon fibers are treated with nitric acid in a 60°C water bath; after treatment, they are washed with distilled water until the pH is close to 7, and dried in a vacuum drying oven at 60°C. The carbon fibers are then immersed in the prepared silane coupling agent hydrolyzate for ultrasonic dispersion for 10 minutes, and the oil bath is heated to 80°C for condensation and reflux for 12 hours, and then filtered and washed to remove the unreacted silane coupling agent on the surface. Place in a vacuum drying oven and dry at a constant temperature of 80°C.
[0063] S2. Preparation of polyimide-based composite materials: The fibers treated in S1 were mixed evenly with the polyimide matrix by a twin-screw extruder to form strips, which were pelletized by a pelletizer. Subsequently, the pellets were hot-molded by an automatic hot press to prepare two standard strips, namely, tensile and bending strips.
[0064] Comparative Example 1
[0065] The difference from Test Example 2 is that the reinforcing material carbon fiber is not treated with a coupling agent, and the other steps are completely the same.
[0066] Comparative Example 2
[0067] The difference from Experimental Example 2 is that the reinforcing material carbon fiber is treated with a small molecule coupling agent KH550, and the other steps are completely the same.
[0068] The results are as follows Figure 2 As shown, Figure 2(a) is the untreated sample, (b) is the sample treated with the small molecule silane coupling agent KH550, (c) is the sample treated with the macromolecular silane coupling agent 6FDA-ODA-KH550, (d) is the sample treated with the macromolecular silane coupling agent a-ODPA-ODA-KH550, and (e) is the sample treated with the macromolecular silane coupling agent a-ODPA-134APB-KH550. The untreated fiber was directly pulled out of the matrix when it broke, with almost no matrix residue, showing a brittle fracture, indicating that the two-phase interface bonding between the fiber and the PI matrix was poor, and the fiber was simply embedded in the PI matrix. After treatment with the small molecule silane coupling agent KH550, there was less resin adhesion on the exposed fiber surface, and the two-phase interface was still clearly visible, indicating that the bonding between the KH550-modified fiber and the PI matrix was still weak. After treatment with the macromolecular silane coupling agent, it can be clearly seen that the fiber surface is covered with a layer of resin, and most of the fibers do not debond, showing a tough fracture. This shows that the macromolecular silane coupling agent improves the compatibility between the fiber and the resin matrix. The treated fibers are evenly distributed in the PI matrix and have the best bonding with the PI matrix.
[0069] like Figure 3 As shown in the figure, the tensile and three-point bending tests were performed on the prepared specimens by a universal testing machine. The results showed that the tensile and bending strengths of the carbon fiber reinforced polyimide composite material without coupling agent treatment were 115.3MPa and 168.9MPa, the tensile and bending strengths after treatment with KH550 were 120.2MPa and 175.6MPa, and the tensile and bending strengths after treatment with macromolecular silane coupling agent were as high as 136.3MPa and 188.8MPa. Compared with small molecule silane coupling agent, macromolecular silane coupling agent has a greater improvement on the mechanical properties of composite materials.
[0070] like Figure 4 As shown, the carbon fiber reinforced polyimide composite material without coupling agent treatment reached 5% thermal weight loss at 499.0℃, and reached 5% thermal weight loss at 499.8℃ after treatment with KH550. The thermal weight loss temperatures of 5% after treatment with macromolecular silane coupling agent were 525.4℃, 509.4℃ and 522.8℃ respectively. Compared with small molecule silane coupling agent, the fiber composite material treated with macromolecular silane coupling agent showed higher thermal stability.
[0071] like Figure 5 As shown in Figure 2, the glass transition temperature of the carbon fiber reinforced polyimide composite material without coupling agent treatment is 256.2℃, and the glass transition temperature (T g ) is 256.9℃, and the glass transition temperatures after treatment with macromolecular silane coupling agent are 258.5℃, 260.0℃ and 258.4℃ respectively.
[0072] Experimental Example 3 Application of macromolecular silane coupling agent in Example 1-3 to modified reinforced glass fiber
[0073] S1. Select 325 mesh glass fiber powder, provided by Lingshou County Jinchang Mineral Products Processing Plant. First, clean the surface of the fiber powder by soaking it in anhydrous ethanol solution for 24 hours, ultrasonically treating it for 30 minutes, and vacuum drying it. Dry it in a vacuum drying oven at 60°C. Immerse the fiber powder in the prepared silane coupling agent hydrolyzate and ultrasonically disperse it for 10 minutes. After heating it in an oil bath to 80°C and condensing and refluxing it for 12 hours, filter and clean it to remove the unreacted silane coupling agent on the surface. Dry it in a vacuum drying oven at a constant temperature of 80°C.
[0074] S2. Preparation of polyimide-based composite materials: The fibers treated in S1 were mixed evenly with the polyimide matrix by a twin-screw extruder to form strips, which were pelletized by a pelletizer. Subsequently, the pellets were hot-molded by an automatic hot press to prepare two standard strips, namely, tensile and bending strips.
[0075] Comparative Example 3
[0076] The difference from Experimental Example 3 is that the reinforcing material glass fiber is not treated with a coupling agent, and the other steps are completely the same.
[0077] Comparative Example 4
[0078] The difference from Experimental Example 3 is that the reinforcing material glass fiber is treated with a small molecule coupling agent KH550, and the other steps are completely the same.
[0079] The results are as follows Figure 6 As shown in the figure, the untreated fiber is directly pulled out of the matrix when it breaks. The glass fiber surface is smooth and there is no matrix residue. It shows brittle fracture, indicating that the two-phase interface bonding between the fiber and the PI matrix is poor, and the fiber is simply embedded in the PI matrix. After treatment with the small molecule silane coupling agent KH550, there is little resin adhesion on the exposed fiber surface, and the two-phase interface is still clearly visible, indicating that the bonding between the KH550-modified fiber and the PI matrix is still weak. After treatment with the macromolecular silane coupling agent, it can be clearly seen that the fiber surface is covered with a layer of resin, and most of the fibers do not debond, showing tough fracture, indicating that the macromolecular silane coupling agent improves the compatibility between the fiber and the resin matrix. The treated fiber is evenly distributed in the PI matrix and has the best bonding with the PI matrix.
[0080] like Figure 7As shown in the figure, the tensile and three-point bending tests were carried out on the prepared specimens by a universal testing machine. The results showed that the tensile and bending strengths of the glass fiber reinforced polyimide composite material without coupling agent treatment were 90.7MPa and 144MPa, the tensile and bending strengths after treatment with KH550 were 93.3MPa and 158.3MPa, and the tensile and bending strengths after treatment with macromolecular silane coupling agent were up to 105.9MPa and 168.4MPa. Compared with small molecule silane coupling agent, macromolecular silane coupling agent has a greater improvement on the mechanical properties of composite materials.
[0081] like Figure 8 As shown in the figure, the glass fiber reinforced polyimide composite material without coupling agent treatment reached 5% thermal weight loss at 496.8℃, and after treatment with KH550, it reached 5% thermal weight loss at 521.6℃. After treatment with macromolecular silane coupling agent, the highest thermal weight loss temperature reached 5% at 529.6℃. Compared with small molecule silane coupling agent, the fiber composite material treated with macromolecular silane coupling agent showed higher thermal stability.
[0082] like Fig. 9 As shown, the glass transition temperature of the glass fiber reinforced polyimide composite material without coupling agent treatment is 254.8°C, the glass transition temperature after treatment with KH550 is 255.7°C, and the glass transition temperatures after treatment with macromolecular silane coupling agent are 256.8°C, 257.6°C and 257.2°C respectively.
[0083] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. Application of a macromolecular silane coupling agent for polyimide composite materials in polyimide-based composite materials, characterized in that: The macromolecular silane coupling agent is any one of the following general formulas (I) to (III): ; (Ⅰ) ; (Ⅱ) ; (Ⅲ) In general formula (I) to general formula (III), n≥3, R1, R2, R3 are independently selected from C1~C18 linear or branched saturated alkyl groups, R4 is selected from C1~C18 linear or branched saturated alkyl groups or branched or branched alkanes with heteroatoms; The preparation method of the macromolecular silane coupling agent for the polyimide composite material is as follows: The raw material A and the raw material B are mixed under anhydrous and oxygen-free conditions and added to an organic solvent for reaction, and then end-capped with 2-aminopyridine, a polyimide solution is obtained by chemical imidization reaction, and then ethanol is added to precipitate the polyimide to obtain an end-capped product, and the end-capped product is washed and dried and then subjected to a transfer amidation reaction with the raw material C to prepare a macromolecular silane coupling agent; the chemical imidization reaction is to add a dehydrating agent and a catalyst for reaction; the dehydrating agent is acetic anhydride, and the catalyst is triethylamine or pyridine; The raw material A is a diamine, the raw material B is a dibasic acid anhydride, and the raw material C is a silane coupling agent with an amino terminal group; the diamine is diaminodiphenyl ether or 1,3-bis(4-aminophenoxy)benzene; and the dibasic acid anhydride is hexafluorodianhydride or 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride.
2. The use of a macromolecular silane coupling agent for polyimide composite materials according to claim 1 in polyimide-based composite materials, characterized in that: The organic solvent is one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, xylene and tetrahydrofuran.
3. The use of a macromolecular silane coupling agent for polyimide composite materials according to claim 1 in polyimide-based composite materials, characterized in that: The reaction temperature of the raw material A and the raw material B is 80-140°C, and the reaction time is 4-6h; The molar ratio of raw material A to raw material B is 1:0.75-1.
4. The use of a macromolecular silane coupling agent for polyimide composite materials according to claim 1 in polyimide-based composite materials, characterized in that: The reaction temperature of the capped product and the raw material C is 80-140 ℃, and the reaction time is 12-24h; The molar ratio of the end-capping product to the raw material C is 1:1-3.
Citation Information
Patent Citations
Class of super heat-resistant imide aromatic heterocyclic modified silane coupling agent
CN101775140A